The Importance of Developing our Teaching Philosophy as EFL Professionals - Espinoza Campos, Jorge Luis (Revista Ensayos Pedagógicos, 2012)
Creating our own teaching philosophy statement is an innovative practice, and it should be a meaningful part for teachers since it states the learning experiences, goals, beliefs, level of professionalism and self development among many other elements. Some teachers usually write a teaching philosophy statement just to carry out a school assignment or to complete their résumé. However, in real life, teachers do not often implement all the nice ideas that are stated in their teaching philosophy statement. The goal of this paper is to make EFL teachers reflect on the importance of developing this practice in the foreign language teaching field to show their learning and growth throughout time.